2010
DOI: 10.1177/1933719110379920
|View full text |Cite
|
Sign up to set email alerts
|

Basal and Steroid Hormone-Regulated Expression of CXCR4 in Human Endometrium and Endometriosis

Abstract: Endometriosis is associated with activation of local and systemic inflammatory mechanisms, including increased levels of chemokines and other proinflammatory cytokines. We have previously reported increased gene expression of chemokine receptor 4 (CXCR4), the receptor for CXCL12, in lesions of the rat model of endometriosis. The CXCR4-CXCL12 axis has been shown to have both immune (HIV infection, lymphocyte chemotaxis) and nonimmune functions, including roles in tissue repair, angiogenesis, invasion, and migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 64 publications
4
41
0
Order By: Relevance
“…32 ). These data are consistent with results published by Ruiz et al who also found significantly higher CXCR4 expression in endometriotic lesions compared to normal endometrium 33 . In 2012 Ji published that macrophages act as a direct structure contributor to lymphatic endothelial walls or secrete a vascular endothelial growth factor (VEGF) to initiate lymphangiogenesis in inflamed or tumor tissues 34 .…”
Section: Discussionsupporting
confidence: 83%
“…32 ). These data are consistent with results published by Ruiz et al who also found significantly higher CXCR4 expression in endometriotic lesions compared to normal endometrium 33 . In 2012 Ji published that macrophages act as a direct structure contributor to lymphatic endothelial walls or secrete a vascular endothelial growth factor (VEGF) to initiate lymphangiogenesis in inflamed or tumor tissues 34 .…”
Section: Discussionsupporting
confidence: 83%
“…40 Microarray studies that show the increased mRNA expression of both CXCR4 and CXCL12 in endometriotic lesions further support our results. 1,35 Bone marrow (BM) contains multiple cell types including mesenchymal stem cells, which have the capacity to differentiate into a number of numerous types of cells.…”
Section: Cxcr4supporting
confidence: 79%
“…These results are in agreement with the previous reports, 11,24,34,35 which described the upregulation of CXCR4 in both ectopic and eutopic endometrium of patients with endometriosis, as well as in endometriotic lesions in a rat model of endometriosis 34 and the peritoneal fluid from endometriosis patients. [36][37][38] More recently, it is been reported that the activation of the CXCR4-CXCL12 signaling axis is involved in the pathophysiology of endometriosis by promoting invasion and growth of endometrial cells ectopically 39,40 and is responsible for the survival of human secretory phase endometrial stromal cells by the inhibition of autophagy. 41 We demonstrated previously that E2 treatment at physiological levels induced the expression of both CXCR4 and CXCL12 in mBMCs and in human endometrial stromal cells (hESCs), respectively, and enhanced the chemoattraction activity of Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to EEC, Hs832cT cells have a lower ER1/ER2 ratio and lower PR protein levels (Bello et al, unpublished data). Steroid hormone treatments were conducted as described by Ruiz et al 23 …”
Section: Cell Culture and Ovarian Steroid Hormone Treatmentsmentioning
confidence: 99%